Mortality and cardiovascular and respiratory morbidity in individuals with impaired FEV 1 (PURE): an international, community-based cohort study - Duong, MyLinh; Islam, Shofiqul; Rangarajan, Sumathy; Leong, Darryl; Kurmi, Om; Teo, Koon; Killian, Kieran; Dagenais, Gilles; Lear, Scott; Wielgosz, Andreas; Nair, Sanjeev; Mohan, Viswanathan; et al. (The Lancet global health, 2019)
The associations between the extent of forced expiratory volume in 1 s (FEV ) impairment and mortality, incident cardiovascular disease, and respiratory hospitalisations are unclear, and how these associations might vary across populations is unknown. In this international, community-based cohort study, we prospectively enrolled adults aged 35-70 years who had no intention of moving residences for 4 years from rural and urban communities across 17 countries. A portable spirometer was used to assess FEV . FEV values were standardised within countries for height, age, and sex, and expressed as a percentage of the country-specific predicted FEV value (FEV